Kewenangan Pemerintah Daerah untuk Melindungi Bidan yang Melaksanakan Program Keluarga Berencana - Anggraeni Novitasari Ujianingtyas (Faculty of Law Hang Tuah University, 2023)
Since midwife as front liner for family planning endure many risks, The Local Government must protect them from any chance of sue. This study is analyze midwife authority due to family planning programs, and analize Local Government authority to protect midwifes that servicing a family program. This is a juridical normative studiy with a statue approach, comparative approach and conceptual approach. The result of the study shows that the Local Government must protect midwifes by assign an innovation regulation. The regional head regulation may consist engangement of religious leader to help promoting family planning service. Many guidelines and manuals must be made in order to protect obedient midwifes. And push KORPRI to make a Legal Consulting and Aid Institute. The making of family planning regulation must be honor the human rights.